2009
DOI: 10.1123/jpah.6.5.617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using a Treadmill Workstation on Performance of Simulated Office Work Tasks

Abstract: Although using a treadmill workstation may change the sedentary nature of desk jobs, it is unknown if walking while working affects performance on office-work related tasks.Purpose:To assess differences between seated and walking conditions on motor skills and cognitive function tests.Methods:Eleven males (24.6 ± 3.5 y) and 9 females (27.0 ± 3.9 y) completed a test battery to assess selective attention and processing speed, typing speed, mouse clicking/drag-and-drop speed, and GRE math and reading comprehensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 27 publications
11
86
1
3
Order By: Relevance
“…Of the 112 work-related outcomes that were measured, 21 worsened. Of these, 16 were reported in studies using treadmill desks (36,41,46,48,51), with the other five reported in studies using cycle ergometers (46,53). A recent study suggested that a certain acclimatization period may be necessary for the improvement of work performance parameters when such activity-permissive workstations are used (75).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 112 work-related outcomes that were measured, 21 worsened. Of these, 16 were reported in studies using treadmill desks (36,41,46,48,51), with the other five reported in studies using cycle ergometers (46,53). A recent study suggested that a certain acclimatization period may be necessary for the improvement of work performance parameters when such activity-permissive workstations are used (75).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the possible floor effects, it was still found that participants in the walking group had significantly worse reading comprehension scores than those in the sitting group. This finding is in direct contrast to previous research comparing GRE reading comprehension tests while walking and sitting, which found no differences between the groups (John et al, 2009), although their study involved desktop computers as opposed to a mobile device. The current study seems to be more in line with research done on mobile devices showing that there is a noticeable drop off in reading comprehension when comparing sitting with walking (Bernard et al, 2007;Chen & Lin, 2016), and in general performance involved with walking (Kane et al, 2008;Mackay et al, 2005;Schildbach & Rukzio, 2010).…”
Section: Summary Of Findingscontrasting
confidence: 99%
“…While it is apparent that walking has a detrimental effect on reading comprehension in the Bernard et al (2007) study, conflicting results were reported in a different study (John, Bassett, Thompson, Fairbrother, & Baldwin, 2009). Their study evaluated the benefits of using a treadmill workstation in comparison to a typical sitting workstation.…”
Section: Reading While Walkingmentioning
confidence: 93%
“…Previous researches on active workspaces have reported positive outcomes over a short period, although the results occasionally depended on the type of work performed. Some studies have shown that walking while working leads to an increase in energy expenditures for many individuals [17,18]; however, while mouse use and typing tasks resulted in more errors over a more extended period of time [19][20][21][22], these activities did not affect mental performance [19,20,23].…”
Section: Introductionmentioning
confidence: 97%
“…Cycling and stepping while working may lead to increased energy expenditures when compared to sitting or walking [19,24]. Nevertheless, the use of more intensive cycling leads to greater numbers of task performance errors [21].…”
Section: Introductionmentioning
confidence: 99%